1990
DOI: 10.1111/j.1600-0722.1990.tb00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on mineralization‐related intraoral parameters in periodontitis‐affected and periodontitis‐free adults

Abstract: – The parameters related to an intraoral mineralization tendency in periodontitis‐affected (P+) and periodontitis‐free (P‐) study subjects (16 adults, 46–74 yr, matched for sex and age) were compared. For this purpose the calcium (Ca) and phosphate (P) concentration of both plaque and saliva, resting pH and the acidogenic response of interdental plaque, plaque wet weight, salivary flow rate, buffering capacity and sucrase activity, interdental and salivary S. mutans levels as well as salivary lactobacilli and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
28
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 22 publications
6
28
0
2
Order By: Relevance
“…While a study conducted by Endre kiss reported no change in flow rate with age and showed that flow rate did not correlated with calcium concentration; no such criteria were not evaluated in the present study. (29) Salivary ph reported no statistically significant difference; these results were in accordance with study of Sudhir Shetty et al (7) Salivary Ph has a crucial role in homeostasis of calcium in saliva ; ph increase favour calcium deposition as sub gingival band of calculus and decrease in ph favours dissolution of calcium from hydroxyappetite crystals of enamel leading to dental decay. Results of present study give evidence that individuals with increased salivary parameters ; i.e.…”
Section: Disscussionsupporting
confidence: 85%
See 3 more Smart Citations
“…While a study conducted by Endre kiss reported no change in flow rate with age and showed that flow rate did not correlated with calcium concentration; no such criteria were not evaluated in the present study. (29) Salivary ph reported no statistically significant difference; these results were in accordance with study of Sudhir Shetty et al (7) Salivary Ph has a crucial role in homeostasis of calcium in saliva ; ph increase favour calcium deposition as sub gingival band of calculus and decrease in ph favours dissolution of calcium from hydroxyappetite crystals of enamel leading to dental decay. Results of present study give evidence that individuals with increased salivary parameters ; i.e.…”
Section: Disscussionsupporting
confidence: 85%
“…These findings are in accordance with the works of Khalill et al , Sewon La et al and Endre Kiss. (5,28,29) Present study also proposed a linear increase in salivary calcium level with increase in severity of periodontal disease. As the gingival inflammation extended deeper to involve connective tissues and alveolar bone a significant liner increase in salivary calcium was found.…”
Section: Disscussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Moreover, the finding that walking patients had fewer secondary diagnoses and used fewer daily medications than those with poor mobility supports the view that in spite of the probably drug-related reduction in salivary flow (22), some other factors counteracted with the multitude of caries-inducing factors present in the oral cavity of physically inactive patients. One such factor could be a high level of salivary calcium, which has earlier been connected with low caries activity (23)(24)(25). Patients prone to osteoporosis seem to have higher levels of salivary calcium than their healthy controls (26)(27)(28).…”
Section: Discussionmentioning
confidence: 98%